Translation of clinical problems in osteoarthritis into pathophysiological research goals. Issue 1 (26th May 2016) - van der Kraan, Peter M; Berenbaum, Francis; Blanco, Francisco J; Cosimo, de Bari; Lafeber, Floris; Hauge, Ellen; Higginbottom, Adele; Ioan-Facsinay, Andreea; Loughlin, John; Meulenbelt, Ingrid; Moilanen, Eeva; Pitsillidou, Irene; et al.
Abstract : Osteoarthritis (OA) accounts for more disability among the elderly than any other disease and is associated with an increased mortality rate. The prevalence in Europe will rise in the future since this continent has a strongly ageing population and an obesity epidemic; obesity and age both being major risk factors for OA. No adequate therapeutic options, besides joint replacement, are available, although they are greatly needed and should be acquired by adequate research investments. However, the perspective on OA from a researcher's point of view is not always aligned with the perspective of a patient with OA. Researchers base their views on OA mainly on abnormalities in structure and function while patients consider OA as a collection of symptoms. In this viewpoint paper, we discuss the possibility of translating the most important clinical problems into pathophysiological research goals to facilitate the translation from bench to bedside and vice versa. This viewpoint is the outcome of a dialogue within the 'European League Against Rheumatism study group on OA' and People with Arthritis/Rheumatism across Europe (PARE) representatives.